Circularity-based decision-making framework for the integrated conservation of built heritage: the case of the Medina of Tunis - Tira, Yasmine; Türkoğlu, Handan (Springer Science and Business Media LLC, 2023)
AbstractSeveral factors overlap in making urban heritage conservation vulnerable in terms of long-term sustainability. The purpose of this study is to offer insights into the dynamic role that heritage governance plays in the current sustainability debate. This purpose is achieved by investigating the shift from a ‘governing for culture’ approach to a ‘governing through culture’ approach in heritage conservation. Subsequently, a case is built for a circularity-based conservation strategy applicable to the governance of historic cities. Different indicators of the circular governance approach are considered, and useful data are collected in comparative form. The cross-matching relationship between the factors is then evaluated by employing the analytic hierarchy process (AHP) on the collected data. As a test case, the conservation strategy of the Medina of Tunis is presented. For a more general conservation model, case-specific data are acquired. Finally, the same framework is applied to compare the case-dependent and case-independent data to define an integrated conservation framework. The obtained results show that the knowledge and data exchange factor, carries the highest significance. This result translates into heritage-led urban regeneration through knowledge sharing and the effective redistribution of cultural activities in historic city centres.
Keywords: Conservation model; Integrated conservation; NA1-9428; Built heritage; Architecture; The Medina of Tunis historic city; Analytic hierarchy process (AHP); Circular governance